Black American older adults' motivation to engage in osteoarthritis treatment recommendations for pain self-management: A mixed methods study. (April 2021) - Booker, Staja; Herr, Keela; Tripp-Reimer, Toni
Abstract: Background: Osteoarthritis is a long-term condition, and four core treatments are recommended to minimize the interference of pain and symptoms on their daily function. However, older Black Americans have traditionally been at a disadvantage in regard to knowledge of and engagement in chronic disease self-management and self-care. Surprisingly, minimal research has addressed understanding motivational factors key to self-management behaviors. Thus, it is important to understand if older Black Americans' self-management is supported by current recommendations for the management of symptomatic osteoarthritis and what factors limit or motivate engagement in recommended treatments. Objective: Our objectives are to: (1) identify stage of engagement in four core recommended treatments for osteoarthritis, (2) describe the barriers and motivators to these recommended treatments, and (3) construct an understanding of the process of pain self-management motivation. Design: A mixed-methods concurrent parallel design. Setting: Participants were recruited from communities in northern Louisiana, USA. Participants: Black Americans (≥50 years of age) with clinical osteoarthritis and/or provider-diagnosed osteoarthritis were enrolled. One hundred ten participants completed the study, and 18 of these individuals were also interviewed individually. Methods: Data were collected using in-person surveys and interviews. Over a period of 11 months, close- and open-ended surveys and in-depth interviews were conducted with participants. Descriptive statistics describe utilization/engagement level as well as barriers and motivators of recommended treatments for non-surgical osteoarthritis. Content and thematic analyses of interviews summarized perspectives on the process and role of motivation in pain self-management. Results: Overall, engagement levels in treatments ranged from very low to high. Over 55% of older Black Americans were actively engaged in two of the recommended treatments: land-based exercise and strength training. Major motivators included reduction in pain and stiffness and maintenance of mobility and good health. The majority of participants were not using water-based exercise and self-management education. Primary barriers were lack of access, time, and knowledge of resources. Conclusions: In order to maximize the benefits of osteoarthritis pain self-management, older Black Americans must be equipped with the motivation, resources, information and skills, and time to engage in recommended treatment options. Their repertoire of behavioral self-management did not include two key treatments and is inconsistent with what is recommended, predominantly due to barriers that are difficult to overcome. In these cases, motivation alone is not optimal in promoting self-management. Providers, researchers, and community advocates should work collaboratively to expand access to self-management resources, particularly when personal and community motivation are high.